Metabolomic analysis of human plasma from haemodialysis patients - Sato, Emiko; Kohno, Masahiro; Yamamoto, Masanori; Fujisawa, Tatsuya; Fujiwara, Kouichi; Tanaka, Noriaki (European journal of clinical investigation, 2011)
Eur J Clin Invest 2011; 41 (3): 241–255 Background  Urea and creatinine are widely used as biomarkers for disease. However, these parameters have been criticized as markers for several reasons. Thus, we conducted this study to identify novel biomarkers that can be used as alternatives to urea and creatinine to estimate the adequate dialysis dose by metabolomic analyses of plasma samples from patients undergoing haemodialysis. Material and methods  Liquid chromatography–electrospray ionization (ESI)–time‐of‐flight mass spectrometry (MS) was used to analyse low molecular weight molecules present in the plasma samples of 10 patients with end‐stage renal disease (ESRD) who were being treated with haemodialysis, and in 16 healthy subjects. Results  In plasma samples obtained after haemodialysis, the relative quantities of 54 peaks were significantly (P < 0·05) decreased when compared with those in the plasma before haemodialysis. The candidate biomarkers were allocated to three groups. Molecules in Group A improved completely with a large variance, molecules in Group B improved partially but with a large variance, and molecules in Group C improved partially with low variance after haemodialysis. Small cohort validation study consisting of the patients with ESRD undergoing haemodialysis indicates that three candidate biomarkers in Group C would be a very useful marker to estimate adequate haemodialysis dose. Conclusions  1‐Methylinosine and two unknown molecules whose m/z at ESI‐positive mode are 257·1033 and 413·1359 were found as effective candidate biomarkers to estimate adequate haemodialysis dose, which has to be confirmed in prospective studies.